Ghrelin-induced Food Intake, but not GH Secretion, Requires the Expression of the GH Receptor in the Brain of Male Mice - Wasinski, Frederick (2021)
Ghrelin stimulates both GH secretion and food intake. The orexigenic action of ghrelin is mainly mediated by neurons that coexpress agouti-related protein (AgRP) and neuropeptide Y (NPY) in the arcuate nucleus of the hypothalamus (ARH). GH also stimulates food intake and, importantly, ARHAgRP/NPY neurons express GH receptor (GHR). Thus, ghrelin-induced GH secretion may contribute to the orexigenic effect of ghrelin. Here, we investigated the response to ghrelin in male mice carrying GHR ablation specifically in neurons (brain GHR knockout [KO] mice) or exclusively in ARHAgRP/NPY neurons (AgRP GHR KO mice). Although brain GHR KO mice showed normal ghrelin-induced increase in plasma GH levels, these mutants lacked the expected orexigenic response to ghrelin. Additionally, brain GHR KO mice displayed reduced hypothalamic levels of Npy and Ghsr mRNA and did not elicit ghrelin-induced c-Fos expression in the ARH. Furthermore, brain GHR KO mice exhibited a prominent reduction in AgRP fiber density in the ARH and paraventricular nucleus of the hypothalamus (PVH). In contrast, AgRP GHR KO mice showed no changes in the hypothalamic Npy and Ghsr mRNAs and conserved ghrelin-induced food intake and c-Fos expression in the ARH. AgRP GHR KO mice displayed a reduced AgRP fiber density (∼16%) in the PVH, but this reduction was less than that observed in brain GHR KO mice (∼61%). Our findings indicate that GHR signaling in the brain is required for the orexigenic effect of ghrelin, independently of GH action on ARHAgRP/NPY neurons.